Exterior condensations on facades: numerical simulation of the undercooling phenomenon - E. Barreira (2013)
This article intends to apply existing numerical models of exterior boundary conditions on the simulation of exterior condensation on facades (undercooling phenomenon) finished with external thermal insulation composite systems. The results of three hygrothermal models were compared, regarding the temperature on the exterior surface of a west facade. The climatic conditions from Porto city were used. We analysed in detail how the simulation of the undercooling phenomenon is influenced by the numerical treatment of the radiative balance on the exterior surface. The numerical results show that these programs are useful tools in assessing the exterior condensation on facades and the importance of radiative balance on the exterior surface temperature. However, some differences were observed in the calculated values due to different parameters included in the radiative balance of the models.